Peran Strategi Kepemimpinan Dalam Upaya Meningkatkatkan Kualitas Kinerja Pegawai Pada Instansi Balai Penjaminan Mutu Pendidikan (BPMP) Sumatera Utara - Jubaidah, Siti; Rahmani, Nur Ahmadi Bi (Fakultas Sains & Teknologi, Universitas Labuhanbatu, 2023)
Leadership is important in order to solve problems and provide morale to employees who work. Based on the problems that have been presented above, it is clear that the Office of the North Sumatra Education Quality Assessment Center has not met the right governance. Problems like this should be immediately addressed and maximized to be better in the future so that it can be in accordance with the expected performance results as they should. If this is overcome, it certainly creates a comfortable and conducive atmosphere so that employees can perform their job responsibilities properly and optimally. In the implementation of the work required attitude discipline time, can receive suggestions, respect colleagues, be polite and more diligent to mengetahuin new things. Knowledge and information during this field work practice hopefully can help me as a provision after graduation and plunge in the world of work. This section contains conclusions which are a summary of the results of performance analysis in the previous section.